Neuropsychotoxicity of Abused Drugs: Potential of Dextromethorphan and Novel Neuroprotective Analogs of Dextromethorphan With Improved Safety Profiles in Terms of Abuse and Neuroprotective Effects - Eun-Joo Shin; Phil Ho Lee; Hyun Ji Kim; Toshitaka Nabeshima; Hyoung-Chun Kim (Elsevier, 2008)
Drug abuse involving dextromethorphan, an antitussive, has been a social problem in various geographic locations since the 1960s. Ironically, high doses of the drug confer neuroprotective activity with central nervous system and behavioral effects. Accumulating evidence suggests that metabolism to phencyclidine-like dextrorphan is not essential for the neuroprotective activity of dextromethorphan. Here, we review the neuroprotective properties of dextromethorphan and its potential for abuse and the potential neuroprotective effects of the drug's analogs and 3-hydroxymorphinan, a metabolite of dextromethorphan. These compounds may provide a novel therapeutic direction for the treatment of neurodegenerative diseases such as convulsive or parkinsonian-like disorders. Keywords:: drugs of abuse, dextromethorphan and its analog, phencyclidine-like dextrorphan, 3-hydroxymorphinan, neuroprotective effect